Electrochemical Behaviour of High Stress Steel (AISI 4340) in CO2 Environments with the Presence of H2 Gas - Panca Asmara, Yuli; Siregar, Januar Parlaungan; Cionita, Tezara; Juliawati, Alias (Trans Tech Publications Ltd, 2015)
This research studied the effect of CO2 and H2 gas on electrochemical behaviour of high stress steel (HSS) by using scan polarization graph to measure corrosion rate, corrosion potential and pitting potential. The tensile test samples with and without notches were tested under constant stress of 20% and immersed in 3% NaCl solutions. During experiments, CO2 gas was injected into the samples. To generate H2 gas, the samples were employed cathodically over potential at - 1700 mV (Ag/AgCl) for three days. The results indicated that both CO2 and H2 gases have increased the corrosion rate. Potentiodynamic graph showed that there were changes in pitting potential where the effect of CO2 gas would decrease the pitting potential. However, the presence of the notch did not show any significant difference in corrosion rate.